Signatures of consolidated superparamagnetic and spin-glass behavior in magnetite-silver core-shell nanoparticles - Singh P.; Shukla M.; Upadhyay C. (My University, 2025)
A detailed investigation of magnetization relaxation for silver-coated magnetite nanostructures with three different types of magnetic behavior in a single particle is presented. Magnetite nanoparticles of diameter ∼6.5 nm synthesized via single-phase emulsion were further coated with a silver shell of thickness ∼2 nm. The synthesized nanoparticles are found to be efficiently photoluminescent. The coating of silver generates a magnetically disordered spin layer at the interface of the magnetic core and the non-magnetic shell. This intermediate layer plays a significant role in the dynamical magnetic response of nanoparticles under an external magnetic field. We present detailed magnetic measurements such as field- and temperature-dependent dc magnetization with zero-field-cooled and field-cooled protocols, ac susceptibility and time decay of magnetization relaxation along with their analysis using various formalisms viz. Néel-Arrhenius, Vogel-Fulcher and power law models. The relaxation analysis suggests the consolidated presence of two characteristic relaxation times corresponding to the superparamagnetic and spin-glass behavior of silver-coated magnetite nanoparticles. © 2018 The Royal Society of Chemistry.